2006
DOI: 10.1080/15419060600631474
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gap Junction Coupling Through the Neuronal Connexin Cx35 by Nitric Oxide and cGMP

Abstract: Gap-junctional coupling among neurons is subject to regulation by a number of neurotransmitters including nitric oxide. We studied the mechanisms by which NO regulates coupling in cells expressing Cx35, a connexin expressed in neurons throughout the central nervous system. NO donors caused potent uncoupling of HeLa cells stably transfected with Cx35. This effect was mimicked by Bay 21-4272, an activator of guanylyl cyclase. A pharmacological analysis indicated that NOinduced uncoupling involved both PKG-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…We conclude that Ser-110 and Ser-293 are the main phosphorylation sites in the Cx36 protein. This is in accordance to Patel et al (27), whose experiments with the fish ortholog Cx35 showed the same prevalence in the orthologous phosphorylation sites used. The PKA consensus motifs containing Ser-306 and Ser-315 seem to be used to a lesser extent.…”
Section: The Cytoplasmic Domains Of Cx36 Are Phosphorylated Insupporting
confidence: 92%
“…We conclude that Ser-110 and Ser-293 are the main phosphorylation sites in the Cx36 protein. This is in accordance to Patel et al (27), whose experiments with the fish ortholog Cx35 showed the same prevalence in the orthologous phosphorylation sites used. The PKA consensus motifs containing Ser-306 and Ser-315 seem to be used to a lesser extent.…”
Section: The Cytoplasmic Domains Of Cx36 Are Phosphorylated Insupporting
confidence: 92%
“…Second, the two identified regulatory phosphorylation sites appear to be targets for a number of signaling pathways in addition to the cAMP/PKA pathway. We have found that PKG also phosphorylates both of these sites in vitro (Patel et al, 2006). These sites are also consensus phosphorylation sequences for Casein Kinase II, Ca 2+ -Calmodulin-dependent kinases, and S6 Kinase II (summarized in figure 1; see also Sohl et al, 1998;Urschel et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…The nitric oxide/cGMP/PKG pathway has also been shown to affect Cx35 phosphorylation, and several other signaling pathways are predicted to (Patel et al, 2006). This raises the possibility that phosphorylation of the giant gap junctions is influenced by transmitters other than dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 However, it remains to be determined if there is any interaction between NO and connexins in the testes. Also, NO has a negative role in modulating integrin-linked kinase, a protein kinase related to the integrin-associated protein complex, in rat kidneys 46 (Table 2).…”
Section: Nos/no and Spermatogenesismentioning
confidence: 99%